From high-risk sports to sports as high risk: Crisis, captulation and creativity during COVID-19 (Alternation African Scholarship Book Series, 5, 2020)
Sadhana Manik: Editorial: From High-risk Sports to Sports as High Risk: Crisis, Capitulation and Creativity during COVID-19 Francois Johannes Cleophas and Lesley Le Grange: A Critique of Neoliberalism in Sport: Towards Optimistic Sport in the Wake of the COVID-19 Pandemic Sabelo Abednego Nxumalo: The Conundrum of COVID-19 and the Sports Industry: When Saving Lives is More Important than Entertainment Omar Esau: The Impact of COVID-19 on Chess in South Africa Renuka Ramroop and Jesika Singh: Natural Learning and Fencing: A Case Study of Two Fencers` Lockdown Training Programme during the COVID-19 Pandemic Sadhana Manik: An Auto Ethnographic Optic: Experiences of Migration to Multiple Modes of Training and Participation in Karate during COVID-19 Bellita Banda Chitsamatanga, Wayne Malinga and Nqobile Sikhosana: `Life without Sports`: Socio-Economic Impacts of COVID-19 on South African Society from a Football Lens Kimara Singh and Rachael Jesika Singh: The Experiences of Selected Professional Women Rugby and Soccer Players, and Sport Administrators during COVID-19 Everjoy Munyaradzi, Kudzayi Savious Tarisayi and Alphonce Shoshore: The COVID-19 Pandemic and Sport in High Schools: A Case of Selected Schools in Masvingo District Joshua Risiro: Impact of Covid-19 on Sporting Activities and Society in the Mutare Community, Zimbabwe: Negotiating a Bumpy Playground